Reforming the Role of Magistrates: Implications for Summary Justice in England and Wales - Jane Donoghue (The Modern Law Review, 2014)
This paper examines current government proposals to reorient and ‘strengthen’ the function of lay magistrates through the creation of new magisterial responsibilities such as oversight of out of court disposals and greater involvement with local justice initiatives. It is argued that, taken in isolation, these measures will fail to consolidate the role of magistrates in summary justice unless they are enacted alongside other measures which aim to reaffirm the status of lay justices, and which seek to reverse the trend which has prioritised administrative efficiency at the expense of lay justice.